Sharing the burden: A neutral approach to socioecological theory. (30th January 2018) - Génin, Fabien; Masters, Judith C.
Abstract: Objective: The socioecological model (SEM) is a popular collection of controversial models purporting to explain mating systems in terms of ecological and social parameters. Despite its guise of objectivity, several of its hypotheses assume Victorian gender stereotypes of active, competing males heedlessly sowing their seeds, and cautious, passive females, imprisoned by greater costs of reproduction and their consequent resourceߚdependence. Methods: We enter this debate by taking a previously neglected explanatory approach borrowed from species theory. According to the Recognition Concept of sexual species, the unit of reproductive success/fitness is irreducible to fewer than two integrated subparts (minimally a male and a female). Phyletic changes in mating systems logically effect changes in fertilization systems, leading to reproductive isolation. We take our primary assumption of the average equivalence of female and male contributions to successful reproduction from the writings of the natural philosopher, Antoinette Blackwell. Results: We revisit the SEM with its contradictions and extrapolations, and develop a genderߚneutral alternative hypothesis termed SpecificߚMate Contact (SMC), centered on two fundamental mating strategies: sexual animals may behave as synchronous mateߚattractors or asynchronous mateߚseekers, generating four possible mating system combinations (monogamy: two attractors; promiscuity: two seekers; polygyny: male attractor and female seeker; polyandry: female attractor and male seeker). Conclusions: Our approach predicts all known primate mating systems using a neutral (nonߚsexist) principle. The approach is also neutral in the sense that it does not invoke either competition or cooperation: fertilization success is considered a posteriori and males and females are coߚadapted to this end rather than cognitively cooperative.